THE EFFECTS OF PARAMETTERS IN CONDITIONAL SAM TABLE ON CONTROL APPROACH USING HEDGE ALGEBRAS - Minh, Nguyễn Duy (Vietnam Journal of Science and Technology, 2012)
SUMMARY Conditional SAM table in control problem which has been studied in [11] shows that the removal of semantic rules isn’t satisfied with properties of dynamical system is correct. However to satisfy with properties and constraints of dynamic system, parameters ∆f1 and ∆f2 (quantified semantic adjust parameter) are given in to conditional SAM table. These parameters with qualitative properties don’t improve that the control error is the smallest. This paper analyzes the effects of two parameter in SAM table on control method using hedge algebras. Besides, it proposes the solution to identify quantified semantic adjust parameters and shows that control using hedge algebras is the most effective method and with this method, the control error is the smallest. So, the content of the pager identifies quantified semantic adjust parameters in order to create a new table ( called optimal SAM table ) satisfying with the constraints and the smallest control error.